Odpowiedzi

Najlepsza Odpowiedź!
2010-02-15T22:47:39+01:00
A) 1-a-a+1 = 2-2a
b) -2a+6-6+6a = 4a
c) nie ewiem czy dobrze zapisales / as to zadanie sprawdz jeszcze raz

3x +6 +x²-2x(x²-x)-1-3
3x³-3x²+6x²-6x+ x(do czwartej) -x³-2x³+2x²-4
x (do czwartej) +5x²-6x -4
2010-02-15T22:47:47+01:00
A) (1-a)-(a-1)=1-a-a+1=2-2a
b) -2(a-3)-3(2-3a)=-2a+6-6+9a=7a
c) (3-x)x+2 (x²-x)- 5(0,2 - 0,6x)=3x-2x+2x2-2x-1+3=-x +2xkwadrat+2
1 3 1
2010-02-15T22:50:18+01:00
A) (1-a)-(a-1) = 1-a-a+1 = 2-2a
b) -2(a-3)-3(2-3a)= -2a+6-6+9a = 7a
c) (3-x)x+2 (x²-x)- 5(0,2 - 0,6x) = 3x - x² +2x² -2x - 1+3x = x²+4x-1
1 5 1